(untitled) (Annals of Medical Research, 2021)
Aim: Living kidney donation is important due to the shortage of organ donors in Turkey. Classic retroperitoneal open donor nephrectomy is more beneficial as it can prevent intraperitoneal organ injuries and postoperative adhesion formation. Here we have presented our initial experience about donors who were undergone open donor nephrectomy.